ARTIFICIAL INTELLIGENCE AND THE EROSION OF EDUCATIONAL INTEGRITY: A CALL FOR ACTION - A. Gusti Efendy; Novita Pratiwi; Vemmy Maidita Nur Aisyiah (Tadulako University, 2025)
The widespread adoption of artificial intelligence (AI) across contemporary society has fundamentally changed the educational landscape. However, this technological advancement introduces significant challenges to the fundamental pillar of academia: academic integrity. This research systematically examines the rapid rise of AI-generated academic work, its implications for pedagogical methods, and the resulting erosion of scholastic standards. By conducting a systematic review of current scholarly literature, this study identifies the principal components and potential ramifications of this complex issue. The investigation stresses the need for a comprehensive framework to defend academic integrity while concurrently capitalizing on AI's potential benefits. This research proffers evidence-based guidelines to contribute to the preservation of intellectual honesty in the digital age.